A large scale hearing loss screen reveals an extensive unexplored genetic landscape for auditory dysfunction - Michael R. Bowl (Nature Portfolio, 2017)
The full extent of the genetic basis for hearing impairment is unknown. Here, as part of the International Mouse Phenotyping Consortium, the authors perform a hearing loss screen in 3006 mouse knockout strains and identify 52 new candidate genes for genetic hearing loss.